Necessity of arbitration - Spohr, Bertha J. (My University, 1898)
Introduction: “War is the organization and exercise of the combative instincts of man common to him and beasts.” With the progress of science and civilization its methods have varied, but through all history, it has recorded the desolation of countries and the massacre of prisoners. It has also recorded the perpetration of barbarity and the slavery of women and children of the conquered nation. It cannot be denied that war extended civilization in ancient times, and that Rome and Greece did much to subdue barbarism and civilized nations. It was necessary that the Persians be subdued from their contempt of the just restraints of law, morality, and civility. The common wealth of Greece were welded into a more powerful state just as the American War of Independence showed the weakness of confederate states, and united them into one of the great nations of the world. In ancient times war was the chief means of bringing nations together.
Citation: Spohr, Bertha J. Necessity of arbitration. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: War; Man; Science; Civilization; Greece; Rome; Persians; Theses; Manuscripts (documents)